2015
DOI: 10.5032/jae.2015.04031
|View full text |Cite
|
Sign up to set email alerts
|

Career and Family Balance of Texas Agricultural Science Teachers by Gender

Abstract: With the high rates of agricultural teacher burnout and attrition in the United States, the need for teachers to strike a balance between their work and family responsibilities is imperative. The purpose of this research study was to explore the influence of gender on Texas agricultural teachers’ perceived job obligations and family responsibilities. Utilizing an online survey instrument, a census of agricultural science teachers in Texas for the 2013-2014 school year was attempted. A total of 567 Texas agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 14 publications
7
23
1
1
Order By: Relevance
“…This is often due to the out-of-classroom expectations, also a leading attrition factor in this study. This finding is supported by the literature that indicates agriculture teachers work well beyond the 40-hour work week and often struggle to balance their personal and professional time (Hainline et al, 2015;Lambert et al, 2011;Murray et al, 2011;Sorensen et al, 2016a;Torres et al, 2008). It is plausible to consider that attrition rates might decline if those in the profession (i.e., Agricultural Education State Staff, CTE Directors, Administrators) made a conscious effort to either (a) decrease the expectations placed upon its teachers, or (b) provide them with additional help/resources to manage the excessive workload.…”
Section: Conclusion and Recommendationssupporting
confidence: 58%
See 2 more Smart Citations
“…This is often due to the out-of-classroom expectations, also a leading attrition factor in this study. This finding is supported by the literature that indicates agriculture teachers work well beyond the 40-hour work week and often struggle to balance their personal and professional time (Hainline et al, 2015;Lambert et al, 2011;Murray et al, 2011;Sorensen et al, 2016a;Torres et al, 2008). It is plausible to consider that attrition rates might decline if those in the profession (i.e., Agricultural Education State Staff, CTE Directors, Administrators) made a conscious effort to either (a) decrease the expectations placed upon its teachers, or (b) provide them with additional help/resources to manage the excessive workload.…”
Section: Conclusion and Recommendationssupporting
confidence: 58%
“…One-third of agriculture teachers indicated a perceived challenge to achieve work-life balance, which raises concern for the profession (Murray, Flowers, Croom, & Wilson, 2011). While some literature confirmed the battle for teachers of agriculture to achieve work-life balance (Hainline, Ulmer, Ritz, Burris, & Gibson, 2015;Sorensen & McKim, 2014), other researchers have determined that agriculture teachers perceive themselves as capable of achieving work-life balance (Clark, Kelsey, & Brown, 2014;Sorensen & McKim, 2014;Sorensen, McKim, and Velez, 2016). Furthermore, researchers found a predictive relationship between teachers' perceptions of increased workload that interferes with family life and the probability of leaving the profession of teaching (Sorensen, McKim, & Velez, 2016).…”
Section: Personal Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural education researchers have attempted to identify issues and isolate factors leading to the teacher attrition problem within the agricultural education profession. Several of the factors include: stress (Lambert, Henry, & Tummons, 2011;Myers, Dyer, & Washburn, 2005;Torres, Lawver, & Lambert, 2009), burnout (Chenevey, Ewing, & Whittington, 2008;Croom, 2003;Kitchel et al, 2012), the inability to balance work with family life (Blackburn, Bunch, & Haynes, 2017;Boone & Boone, 2009;Hainline, Ulmer, Ritz, Burris, & Gibson, 2015;Mundt & Connors, 1999;Murray, Flowers, Croom, & Wilson, 2011;Myers et al, 2005;Sorensen, McKim, & Velez, 2016a;Sorensen, McKim, & Velez, 2016b), possessing a low degree of self-efficacy (Blackburn & Robinson, 2008;Hasselquist, Herndon, & Kitchel, 2017;Knobloch & Whittington, 2003;McKim & Velez, 2015;Wolf, 2011), inadequate compensation (Boone & Boone, 2009;Lemons, Brashears, Burris, Meyers, & Price, 2015), lack of administrative support (Boone & Boone, 2007;Castillo & Cano, 1999;Kelsey, 2006;Walker, Garton, & Kitchel, 2004), lack of student motivation and poor behavior (Boone & Boone, 2009;Tippens, Ricketts, Morgan, Navarro, & Flanders, 2013), heavy workload (Hainline et al, 2015;Lambert et al, 2011;Murray et al, 2011;Sorensen et al, 2016a), poor working conditions (Boone & Boone, 2007;Castillo & Cano, 1999;…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has demonstrated that measuring career satisfaction using the outcomes of the agricultural education program and the FFA have been both a promotor and a detractor. Hainline, Ulmer, Ritz, Burris, and Gibson (2015) reported the balance between home and professional life may be representative of high attrition and low longevity rates in the agricultural education classroom. Responsibilities focusing on the classroom and the community, time, and commitments away from family are strongly associated with teacher attrition and performance.…”
Section: Introductionmentioning
confidence: 99%